Hollow Carbon Nanopolyhedra for Enhanced Electrocatalysis via Confined Hierarchical Porosity. Issue 23 (28th April 2017) - Song, Xiaokai; Guo, Linli; Liao, Xuemei; Liu, Jian; Sun, Jianhua; Li, Xiaopeng
Abstract : A novel strategy for the fabrication of hollow Co and N‐codoped carbon nanopolyhedra (H‐CoNC) from metal–organic framework (MOF) using in situ evaporation of ZnO nanosphere templates is proposed. The excess Zn supply during the pyrolysis process is found beneficial in terms of high nitrogen (≈9.75 at%), relatively homogenous CoN bonding, and the electrochemically accessible hierarchical porous system. Compared with other reported "solid" CoNC of identical surface areas, the newly developed H‐CoNC shows enhanced kinetic current in 0.1m KOH electrolyte and elevated oxygen reduction reaction (ORR) performance in 6m KOH. The latter exceeds results obtained with the benchmark 20 wt% Pt/C, which is related to the strong confinement of O2 molecules in the H‐CoNC hierarchical porous system. Furthermore, the H‐CoNC displays great tolerance toward the methanol crossover and KSCN poisoning. Finally, the assembled Zn–air batteries with H‐CoNC yield a record open circuit potential (1.59 V vs Zn, stabilized at 1.52 V), high power density (331.0 mW cm −2 ), and promising rate performance. This work provides a new guideline for the design of MOF‐derived carbon materials, as well as novel insights into spatial confinement effect toward the ORR activity. Abstract : A novel strategy for synthesizing hollow Co, N–co‐doped carbon nanopolyhedra from metal–organic frameworks using in situ evaporation of ZnO templates is proposed. The hollow carbon catalyst shows noticeable improvements in electrokinetics, oxygen reduction reaction selectivity/stability, and resistance to CH3 OH, and the corresponding Zn–air battery exhibits a record open circuit potential, thanks to a strong confinement effect.